The gnostic Gospels - Pagels, Elaine H., 1943- (London Penguin Books, 1979)
"A startling account of the meaning of Jesus and the origin of Christianity based on gnostic gospels and other secret texts, written almost 2,000 years ago, recently discovered near Nag Hammadi in Upper Egypt"--Jacket subtitle.
The controversy over Christ's resurrection : historical event or symbol? -- "One God, one bishop" : the politics of monotheism -- God the father/God the mother -- The passion of Christ and the persecution of Christians -- Whose church is the "true church"? -- Gnosis : self-knowledge as knowledge of God.
Includes bibliographical references and index.
Keywords: Apocryphal Gospels; Nag Hammadi codices; Gnosticism